EFFECT OF THE COMPOSITION OF A MINERAL MIXTURE ON THE RATES OF COMMINUTION OF ITS COMPONENTS - Ivanov O.P. (My University, 1989)
Ores are practically always complex mixtures of several minerals that differ greatly in their mechanical properties but are intimately intergrown. Thus, the kinetics of comminution of a mineral in a mixture is a fundamental aspect of engineering mineralogy and the theory of beneficiation.